Development of Android-based Chemistry Learning Media Integrated AIR Model - Sri Setiawaty; Isna Rezkia Lukman; Rizka Imanda; Reza Putra (LPPM Universitas Malikussaleh, 2022)
This study aims to determine the feasibility of chemistry learning media based Android integrated with the AIR (Auditory, Intellectually, Repetition) model that was developed to increase students' cognitive learning outcomes, as well as to determine student readiness with the renewal of learning modes and student responses to the developed learning media. This study uses the type of Research and Development (R&D) research with adapted from Borg & Gall (2007) dan 4-D (Thiagarajan, dkk., 1974) procedural. The learning media product being developed in the form of an android application with a AIR model on chemistry atomic structure concepts. The android application used in this research is the Smart App Creator software. The validity of the media and the quality of the learning media developed obtained the results of an assessment are 85% and 86% (Very Good), then received a positive response from chemistry is 91%, Furthermore the media was developed should be improve cognitive aspect and significantly with a comparison of the average value of the pretest score of 33.00 and posttest of 81.08 to learning outcomes.